Climate, peace, and conflict—past and present: Bridging insights from historical sciences and contemporary research - Sam White; Dominik Collet; Agustí Alcoberro; Mariano Barriendos; Rudolf Brázdil; Pau Castell; Siyu Chen; Cedric de Coning; Dagomar Degroot; Lukáš Dolák; Stefan Döring; Santiago Gorostiza; et al. (Ambio, 2025)
Concern has risen that current global warming and more frequent extreme events such as droughts and floods will increase conflict around the world. This concern has spurred both social science research on contemporary climate, peace, and conflict as well as research in the historical sciences on past climate, weather, warfare, and violence. This perspectives article compares these two fields of scholarship and examines how each may benefit the other. It finds significant convergences in methods and insights across contemporary and historical research as well as persistent patterns in causal pathways between climate and conflict. Contemporary climate, peace, and conflict (CPC) research may sharpen methods and causal models for historical researchers. Historical studies, particularly those informed by contemporary research, may elucidate deep origins and long-term effects of climate-related conflicts. For policymakers and the public, history offers comprehensible ways to make sense of complex and contingent linkages and to construct cogent narratives of the past as well as storylines for the future.